The Accompaniment for the Making of Antiseptic Soap, Hand Sanitizers using Natural Ingredients of Lemongrass, Cymbopogon Citrates, as an Effort to Prevent COVID-19 Virus at Taklim Assembly “Active Tamaddun Community”, Palembang - Mariana; Eddy Roflin; Pariyana; Aufa Muhammad Nadhif; Stella Yosephine Ribka; Tania Ayu M (International Journal Of Community Service, 2021)
During this pandemic, many people are looking for antiseptics to prevent the transmission and spread of Covid-19. WHO has issued guidelines for the producing Hand-Sanitizers using ingredients, such as ethanol or isopropyl alcohol, however, the continuous use of hand sanitizers that contain alcohol and triclosan can cause irritation. Efforts that can be made to reduce the use of alcohol and triclosan in the production of hand sanitizers are to use natural ingredients. One of the natural ingredients that can be used is lemongrass (Cymbopogon citratus). The flavonoid content in lemongrass function as antibacterial by forming complex compounds with extracellular proteins. This community service activity aims to provide training on skills in making antiseptic soap and handsanitiser with lemongrass as an effort to prevent and maintain sanitation to stay healthy in the face of adaptations to new habits during the COVID-19 pandemic.